Vascular complications in 305 severely ill patients with COVID-19: a cohort study - Correia, Rebeca Mangabeira; Santos, Brena Costa; Carvalho, Ana Alyra Garcia; Areias, Libnah Leal; Kuramoto, Danielle Akemi Bergara; Pereda, Mariana Raffo; Aidar, Ana Laura e Silva; Clezar, Caroline Nicacio Bessa; Reicher, Marcello Erich; Amorim, Jorge Eduardo de; Flumignan, Ronald Luiz Gomes; Nakano, Luis Carlos Uta (São Paulo Medical Journal, 2023)
BACKGROUND: Although an association has been made between coronavirus disease 2019 (COVID-19) and microvascular disease, data on vascular complications (other than venous thromboembolism) are sparse. OBJECTIVE: To investigate the vascular complications in severely ill patients hospitalized with COVID-19 and their association with all-cause mortality. DESIGN AND SETTING: This cohort study was conducted at the Universidade Federal de São Paulo, Brazil. METHODS: All 305 consecutive patients diagnosed with COVID-19 and hospitalized in the intensive care unit (ICU) of a tertiary university hospital from April 2 to July 17, 2021, were included and followed up for 30 days. RESULTS: Of these, 193 (63.3%) were male, and the mean age was 59.9 years (standard deviation = 14.34). The mortality rate was 56.3% (172 patients), and 72 (23.6%) patients developed at least one vascular complication during the follow-up period. Vascular complications were more prevalent in the non-survivors (28.5%) than in the survivors (17.3%) group and included disseminated intravascular coagulation (DIC, 10.8%), deep vein thrombosis (8.2%), acrocyanosis (7.5%), and necrosis of the extremities (2%). DIC (adjusted odds ratio (aOR) 2.30, 95% confidence interval (CI) 1.01–5.24, P = 0.046) and acrocyanosis (aOR 5.21, 95% CI 1.48–18.27, P = 0.009) were significantly more prevalent in the non-survivors than in the survivors group. CONCLUSION: Vascular complications in critically ill COVID-19 patients are common (23.6%) and can be closely related to the mortality rate (56.3%) until 30 days after ICU admission. Macrovascular complications have direct implications for mortality, which is the main outcome of the management of COVID-19. REGISTRATION: RBR-4qjzh7 (https://ensaiosclinicos.gov.br/rg/RBR-4qjzh7).